Efeito dos inseticidas organofosforados em LVE de Campo Novo dos Parecis - MT e sua degradação por processo oxidativo avançado. - Silva, Simone Raquel Caldeira Moreira da (2008)
The pesticides analyzed are applied largely at soya and cotton cultures in Mato Grosso state. This research takes in consideration the technological factors at each process and the operational conditions of the treatments utilized for the degradation of the organophophorus and the viability of its application for the descontamination of the agricultural effluents. At the research process, tests were made with AGROSCRE simulator to know the potential soil leach of the methyl parathion, malathion, monocrotophos and metamidophos and the results were compared to the methyl parathion and monocrotrophos, with tests in leach columns by OECD. After initial investigations, essays were made about the soil modifications after contaminations with methyl parathion, malathion, monocrotophos and metamidophos. Solution degradation analyzes were made with the methyl parathion, malathion, monocrotophos and metamidophos by an advanced oxidation process.- eletrochemichal degradation, by oxidation with electrogenerated/electrofenton (H2O2 e H2O2/Fe(II)) hydrogen peroxide. The degradation levels of the tested products and of the principal metabolites were identified by chromatrography of high efficience. The results demonstrated that, among the analyzed products, the methyl parathion and the malathion didn t leach at the soil, with strong possibilities of superficial waters contamination, while monocrotophos and the metamidophos are water soluble and can contaminate the superficial waters. The introduction of the organophosphorus at the soil laboratory tested demonstrated that they changed the physical soil characteristics, modifing its texture and behavior as verified in Casagrande letter. This degradation technical of organophosphorus was efficient to methyl paration and malation as well as to their metabolites paraoxon and malaoxon.